The Role Strengthening Digital Literacy in Educational Institutions Indonesia to Overcome the Dangers Cyberbullying - Faradila Ema Nur Azizah (Universitas Muhammadiyah Enrekang, 2023)
The high number of cyberbullying cases that occur from year to year are rampant among teenagers, adults and even children, all of whom are involved in becoming victims and even perpetrators of cruel crimes committed in cyberspace. This research seeks to explore the efforts that should be made by schools which are seen as a forum for producing superior and civilized children's character so that they are wiser and more professional in operating and using digital, especially in this technological era. Data was collected through observation, interviews and documentation activities at 3 educational institutions in Indonesia. The results of the research show that a massive way that can be done to overcome the main problem of overcoming the dangers of cyberbullying can be done by strengthening the role of educational institutions, namely schools, to be able to provide theoretical understanding and real action in terms of operating and using digital in all areas of school activities, namely by making efforts to interconnect all school academic and non-academic activities on a digital basis.